PLC Networks with In-Band Full-Duplex Relays - Cañete-Corripio, Francisco Javier; Prasad, Gautham; Lampe, Lutz (My University, 2020)
Electromagnetic compatibility regulations impose strict transmit power spectral density limitations on power line communication (PLC) that limits the coverage it can provide.As a consequence, PLC networks, especially those used in smart grid neighborhood area networks, employ one or more repeaters/relays for coverage enhancement. In this paper, we analyze the use of in-band full-duplex (IBFD) operation in relaying for power line networks. We present analyses and numerical results to demonstrate the superior operating performance of IBFD-based relay-aided networks over the legacy half-duplex ones, and contrast the extent of performance enhancement we achieve over using direct links. To estimate such performance,we focus on orthogonal frequency division multiplexing (OFDM) systems, which are standard in PLC. We investigate both decode-and-forward and amplify-and-forward schemes of relaying fordual-hop power line links, and quantify the performance in terms of the attainable data rate under diverse realistic power linechannel and noise conditions. The fundamental analyses provided in this work guide the design of future IBFD relay-aided PLC networks across application scenarios.
Keywords: Comunicación eléctrica; Power Line Communications; In-Band Full-Duplex